Alterations in white matter microstructure in alcohol and alcohol‐polydrug dependence: Associations with lifetime alcohol and nicotine exposure. (18th July 2022) - Agunbiade, Kofoworola; Fonville, Leon; McGonigle, John; Elliott, Rebecca; Ersche, Karen D.; Flechais, Remy; Orban, Csaba; Murphy, Anna; Smith, Dana G.; Suckling, John; Taylor, Eleanor M.; Deakin, Bill; et al.
Abstract: Evidence suggests that alcohol dependence (AD) is associated with microstructural deficits in white matter, but the relationship with lifetime alcohol exposure and the impact of polydrug dependence is not well understood. Using diffusion tensor magnetic resonance (MR) imaging, we examined white matter microstructure in relation to alcohol and polydrug dependence using data from the Imperial College Cambridge Manchester (ICCAM) platform study. Tract‐based spatial statistics were used to examine fractional anisotropy (FA) in a cohort of abstinent AD participants, most of whom had a lifetime history of dependence to nicotine. A further subgroup also had a lifetime history of dependence to cocaine and/or opiates. Individuals with AD had lower FA throughout the corpus callosum, and negative associations with alcohol and nicotine exposure were found. A group‐by‐age interaction effect was found showing greater reductions with age in the alcohol‐dependent group within corpus callosum, overlapping with the group difference. We found no evidence of recovery with abstinence. A comparison of alcohol‐only‐ and alcohol‐polydrug‐dependent groups found no differences in FA. Overall, our findings show that AD is associated with lower FA and suggest that these alterations are primarily driven by lifetime alcohol consumption and cigarette smoking, showing no relationship with exposure to other substances such as cocaine, opiates or cannabis. Reductions in FA across the adult lifespan are more pronounced in AD and offer further support for the notion of accelerated ageing in relation to alcohol dependence. These findings highlight there may be lasting structural differences in white matter in alcohol dependence, despite continued abstinence. Abstract : Alcohol‐dependent participants showed lower fractional anisotropy (FA) within the corpus callosum compared with healthy controls. This change was negatively associated with lifetime alcohol and nicotine exposure, and there was no evidence of FA recovery despite prolonged abstinence. A group‐by‐age interaction was observed, whereby greater age‐related reductions in FA were evident in AD participants, but no further reductions in FA were observed in alcohol‐polysubstance relative to alcohol‐only‐dependent participants.